Aerosol Wall Loss in Teflon film Chambers Filled with Ambient Air - 이승복; 배귀남; 문길주 (한국대기환경학회, 2004)
Aerosol wall loss is an important factor affecting smog chamber experiments, especially with chambers made of Teflon film. In this work, the aerosol wall loss was investigated in 2.5 and 5.8-m³cubic-shaped Teflon film chambers filled with ambient air. The natural change in the particle size distribution was measured using a scanning mobility particle sizer in a dark environment. The rate of aerosol wall loss was obtained from the deposition theory suggested by Crump and Seinfeld (1981). The measured rates of aerosol wall loss were in a good agreement with the theoretical and experimental values given by McMurry and Rader (1985), implying that the electrostatic effect enhances particle deposition on the chamber wall. The significance of aerosol wall loss correction was demonstrated with the photochemical reaction experiments using the ambient air.